2013
DOI: 10.1016/j.neuroimage.2013.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Long term cortical plasticity in visual retinotopic areas in humans with silent retinal ganglion cell loss

Abstract: Visual cortical plasticity induced by overt retinal lesions (scotomas) has remained a controversial phenomenon. Here we studied cortical plasticity in a silent model of retinal ganglion cell loss, documented by in vivo optical biopsy using coherence tomography. The cortical impact of non-scotomatous subtle retinal ganglion cell functional and structural loss was investigated in carriers of the mitochondrial DNA 11778G>A mutation causing Leber's hereditary optic neuropathy. We used magnetic resonance imaging (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Young adult carriers of a mitochondrial DNA mutation causing Leber hereditary optic neuropathy have a loss of macular retinal ganglion cells and thicker visual cortex gray matter [68]. In contrast, older people with progressive retinal damage from glaucoma or macular degeneration have thinning in the corresponding eccentric locations of visual cortex [6972].…”
Section: Discussionmentioning
confidence: 99%
“…Young adult carriers of a mitochondrial DNA mutation causing Leber hereditary optic neuropathy have a loss of macular retinal ganglion cells and thicker visual cortex gray matter [68]. In contrast, older people with progressive retinal damage from glaucoma or macular degeneration have thinning in the corresponding eccentric locations of visual cortex [6972].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical volumes were re-oriented in relation to AC–PC plane and transformed to Talairach (TAL) coordinate system. Afterwards, the cerebral cortex was segmented into the cerebral spinal fluid, gray matter, and white matter using automatic segmentation routines in order to create inflated mesh representations of each hemisphere (d'Almeida et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…In this way, the LPZ corresponds to the retinal scotomata in RP patients and the FPZ corresponds to the spared retina. Cortical thickness was calculated on the V1 regions using the standard procedure of BrainVoyager [see (d'Almeida et al, 2013) for a complete description]. To allow an accurate segmentation of white matter–gray matter and gray matter–cerebral spinal fluid boundary, TAL anatomical data were converted to high-resolution 0.5 × 0.5 × 0.5 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…However, each year, millions of infants worldwide suffer from visual deprivation. These populations face the risk of irreversible amblyopia and numerous vision impairments [34][35][36]. Thus, it is important to investigate the mechanisms of environmental regulation of visual system development and its experience-dependent plasticity, which may provide further evidence to develop a comprehensive method for assessing the visual recovery potential in blind children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the axial overgrowth and myopia caused by visual form deprivation can be manipulated by altering peripheral retinal defocus [42]. In addition, early retinal changes are reflected in retinotopically specific plasticity, which can be assessed by visual cortical thickness [34,43]. Both neurochemical and immunocytochemical experiments in chickens and monkeys suggest that definable retinal neurons participate in the regulatory pathway controlling eye growth [41].…”
Section: Discussionmentioning
confidence: 99%